Antioxidant capacity of underutilized Malaysian Canarium odontophyllum (dabai) Miq. fruit. - Shakirin, Faridah Hanim; Prasad, K. Nagendra; Ismail, Amin; Lau, Cheng Yuon; Azlan, Azrina (Elsevier, 2010)
This study aimed to evaluate the antioxidant capacities of various parts of the dabai (Canarium odontophyllum Miq.) fruit. The antioxidant capacities of C. odontophyllum were evaluated using a β-carotene bleaching assay, ferric reducing antioxidant power (FRAP) and 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assays. Total phenolic content of the dabai fruit was estimated using the Folin-Ciocalteu method. The antioxidant capacities ranked in the following order: skin > flesh. +. skin > flesh > kernel. Our findings show that a high correlation exists between total phenolic content and total antioxidant activity. This indicates that phenolic compounds could be the major contributors to the antioxidant capacity of C. odontophyllum fruit. Therefore, dabai fruit, especially the skin, can be recommended as a major source of natural antioxidants.